More than a game: the impact of decent work on work engagement among athletes through the serial mediation of visions about future and sport anxiety - Horozoğlu, Mehmet Ali; Korkmaz, Ozan (Frontiers in Psychology, 2025)
ObjectiveThis current study examined the serial mediating role of visions about future (hope, optimism, pessimism) and sport anxiety in the relationship between decent work and work engagement among professional athletes.MethodsThe participants were 296 professional athletes (30.1% female, 69.9% male) aged between 18 and 48, actively competing in football, volleyball, or basketball leagues in Türkiye. Participants completed the Decent Work Scale, Visions About Future Scale, Sport Anxiety Scale, and Utrecht Work Engagement Scale. Structural equation modeling and bootstrapping methods were used for data analysis.ResultsThe results revealed that decent work positively predicted hope, optimism, and work engagement, and negatively predicted pessimism. Optimism negatively predicted sport anxiety, while pessimism positively predicted it. Sport anxiety had a significant negative effect on work engagement. Furthermore, optimism, pessimism, and sport anxiety significantly mediated the relationship between decent work and work engagement in a serial manner. Hope did not significantly mediate this relationship.ConclusionThese findings highlight the critical role of professional athletes’ future-oriented cognitions and anxiety levels in translating perceptions of decent work into higher engagement in sport. The study provides valuable insights for psychosocial interventions and organizational policies to enhance athletes’ sustainable careers.